1986
DOI: 10.1144/gsl.sp.1986.022.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology of sandwaves in an oolite shoal complex in the Cadeby (Magnesian Limestone) Formation (Upper Permian) of eastern England

Abstract: Sedimentology of sandwaves in an oolite shoal complex in the Cadeby (Magnesian Limestone) Formation (Upper Permian) of eastern England J. KaldiSUMMARY: Four depositional facies are recognizable in the Sprotbrough Member of the Cadeby Formation (formerly the Lower Magnesian Limestone) in eastern England; they are sabkha, semi-restricted lagoon, oolite shoal complex and open marine shelf. Of these, the oolite shoal complex occupies most of the present outcrop in the Yorkshire Province, i.e. south of the Clevelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…An outline of the lithology and distribution of much of the Permian marine sequence at outcrop in north-east England was given by Sedgwick (1829) and details have been added by the authors of Geological Survey Memoirs and many other workers (see individual site accounts for full references); more recent syntheses are by the writer (Smith, 1970a(Smith, , 1974a(Smith, , b, 1980a(Smith, , b, 1992, Pettigrew (1980), Kaldi (1980Kaldi ( , 1986a, Harwood (1981Harwood ( , 1989, Aplin (1985), Goodall (1987) and Hollingworth (1987). Data from outcrop and boreholes are now sufficient for a lateral succession of facies belts to be recognized in three of the main carbonate rock units and for palaeogeographical maps of these to be attempted [see Kaldi (1980Kaldi ( , 1986a and Harwood (1981Harwood ( , 1989 for parts of the sequence in the Yorkshire Province and Smith (1989) for the full sequence in the Durham and Yorkshire provinces].…”
Section: Late Permian Marine and Associated Strata In North-east Englandmentioning
confidence: 99%
See 2 more Smart Citations
“…An outline of the lithology and distribution of much of the Permian marine sequence at outcrop in north-east England was given by Sedgwick (1829) and details have been added by the authors of Geological Survey Memoirs and many other workers (see individual site accounts for full references); more recent syntheses are by the writer (Smith, 1970a(Smith, , 1974a(Smith, , b, 1980a(Smith, , b, 1992, Pettigrew (1980), Kaldi (1980Kaldi ( , 1986a, Harwood (1981Harwood ( , 1989, Aplin (1985), Goodall (1987) and Hollingworth (1987). Data from outcrop and boreholes are now sufficient for a lateral succession of facies belts to be recognized in three of the main carbonate rock units and for palaeogeographical maps of these to be attempted [see Kaldi (1980Kaldi ( , 1986a and Harwood (1981Harwood ( , 1989 for parts of the sequence in the Yorkshire Province and Smith (1989) for the full sequence in the Durham and Yorkshire provinces].…”
Section: Late Permian Marine and Associated Strata In North-east Englandmentioning
confidence: 99%
“…It is interpreted as marking the site of an offshore field of high-energy subaqueous dunes (Smith, 1968(Smith, , 1970b, sandwaves (Kaldi, 1980(Kaldi, , 1986a or grainstone barriers (Harwood, 1981(Harwood, , 1989, and separates a shallow protected shelf or lagoon to the west from a deeper-water open marine outer shelf to the east. The sedimentology and diagenesis of these rocks was investigated in detail by Kaldi (1980Kaldi ( , 1986a and their mineralization by Harwood (1981Harwood ( , 1986. By analysis of the trends of the prevalent large-scale cross-stratification, Kaldi showed that the sandwaves were constructed mainly by currents from the north-east (i.e.…”
Section: The Sprothrough Membermentioning
confidence: 99%
See 1 more Smart Citation